Towards culturally inclusive healthcare in Peru: Mapping epistemic concepts in contemporary Indigenous Amazonian medicine-Traditional healers' perspectives. - Ilana Berlowitz; Maria Amalia Pesantes; Cynthia Cárdenas Palacios; Chantal Martin-Soelch; Ursula Wolf; Caroline Maake (PLOS Global Public Health)
Peru is among Latin American countries with the largest Indigenous population, yet ethnical health disparities persist, particularly in the Amazon region which comprises 60% of the national territory. Healthcare models that include Indigenous medicine and traditional healers present an important avenue for addressing such inequalities, as they increase cultural adequacy of services, healthcare access, and acknowledge Indigenous Rights for their perspectives to be represented in public healthcare. Understanding the underlying epistemologies of Indigenous medicine is a prerequisite for this purpose. Thus, in order to support Indigenous Organizations and governmental initiatives to develop more inclusive healthcare approaches, the current study investigated key epistemic concepts in Indigenous-Amazonian medicine from the perspective of traditional healers. We conducted systematic in-depth interviews (semi-structured) with a sample of 13 healers of three Peruvian-Amazonian regions (Loreto, Ucayali, San Martín). Data was analysed using manifest qualitative content analysis. Our findings point to an intricate medical system based on a sophisticated understanding of health, illness, and treatment. Indigenous healers described multifactorial aetiology concepts, complex interactions between material and spirit-related aspects of body and nature, diagnosis, and treatment. These often involved carefully designed applications of 'teacher plants', a concept at the heart of this medical system. Furthermore, while the healers considered traditional and biomedicine as complementary systems, they identified the lack of recognition of traditional healers as a primary barrier for collaboration. Indeed, preconceptions and stigma on Indigenous medicine along with a paucity of research, still represent an impediment to countries' ability to respond to Indigenous peoples' health-related expectations and needs, thus maintaining existing inequalities. This work offers a significant contribution to the understanding of Indigenous-Amazonian medicine and perspectives of traditional healers, relevant for Peru and adjacent countries sharing Amazonian territory and cultures. Our findings also highlight Amazonian healers' unique expertise around the therapeutic applications of psychoactives, from which the current revival of clinical scientific interest in psychedelic-assisted therapies may have a great deal to learn.